Legal measures to ensure fair distribution of income for sustainable development of Ukraine - S. S. Pyroha (Bulletin of Kharkiv National University of Internal Affairs)
The article examines the relationship between income distribution and the socio-economic development of the state. It is established that traditional methods of income distribution do not provide for sustainable development and do not correspond to the Constitution of Ukraine, which declares Ukraine a social state. The main regulator of income distribution is the Tax Code. Unfortunately, the current Tax Code of Ukraine does not at all provide for a fair redistribution of income and does not stimulate investment in the production sectors, but encourages the creation of various corruption schemes for evasion and avoidance of taxation, which includes a large-scale shadow economy, illegal export of capital, contraband imports and exports. The article proposes legal methods for overcoming all problems and ensuring accelerated development. To achieve these goals, legislation should contain an comprehensive list of price components. The fair market value (price) is equal to the total added value of the product or service, VAT charged on it and total depreciation at all stages of production and distribution. Added value is the sum of the company's factor incomes: wages and profits. The amount of actually paid taxes from the labor and profit fund determines the actually created added value, on which VAT is calculated, which is paid directly to the Budget at each stage of the movement of goods/services to the final consumer. The amount of added value, VAT and depreciation determines the increase in the market value of goods/services at each stage of production and distribution and corresponds to the amount of taxes, contributions and fees paid precisely by law. The distribution of income in society is determined on the basis of the European Social Charter (revised) and is ensured by the introduction of progressive tax rates on the incomes of individuals and the profits of enterprises. The income tax rate should be determined by the direction of use of profits, and the rate of distributed profit on dividends should be equal to the personal income tax rates. The zero rate does not apply to taxation of dividends.